1991
DOI: 10.1016/s0022-5347(17)38203-4
|View full text |Cite
|
Sign up to set email alerts
|

The Innervation of the Human Prostate Gland—the Changes Associated with Benign Enlargement

Abstract: Different regions of the prostate gland, namely prostatic capsule, peripheral prostate and central prostate (subdivided into proximal (near the bladder neck), distal (near the verumontanum) and midway between these areas) were obtained from 32 obstructed (stable obstructed, n = 8; unstable obstructed, n = 13; acute retention, n = 11) and five control patients. The innervation of these tissues was studied both histochemically to localise acetylcholinesterase activity and immunohistochemically for dopamine-beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 37 publications
2
46
0
1
Order By: Relevance
“…The simultaneous presence of these two catecholamine-synthesising enzymes justifies naming these nerve fibres the noradrenergic ones. A more or less equal density of noradrenergic nerve fibres was found in the mucosa and muscular layer of the BU and SV, which is consistent with the results previously obtained in humans (Gu et al, 1983;Chapple et al, 1991;Hedlund et al, 1997) and pigs (Kaleczyc et al, 1999). It must be mentioned that in other studies of the SV of humans (Gosling and Dixon, 1994; as well as rats (Owman and Sjöstrand, 1965;Moss et al, 1987;Yuri, 1990) and guinea pigs (Owman and Sjöstrand, 1965;Wakade and Kirpekar, 1971;Al-Zuchair et al, 1975) noradrenergic nerve fibres were found only in the muscular layer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The simultaneous presence of these two catecholamine-synthesising enzymes justifies naming these nerve fibres the noradrenergic ones. A more or less equal density of noradrenergic nerve fibres was found in the mucosa and muscular layer of the BU and SV, which is consistent with the results previously obtained in humans (Gu et al, 1983;Chapple et al, 1991;Hedlund et al, 1997) and pigs (Kaleczyc et al, 1999). It must be mentioned that in other studies of the SV of humans (Gosling and Dixon, 1994; as well as rats (Owman and Sjöstrand, 1965;Moss et al, 1987;Yuri, 1990) and guinea pigs (Owman and Sjöstrand, 1965;Wakade and Kirpekar, 1971;Al-Zuchair et al, 1975) noradrenergic nerve fibres were found only in the muscular layer.…”
Section: Discussionsupporting
confidence: 92%
“…The ovine prostate contained VIP-IR nerve fibres in a frequency comparable to the one found in the SV and BU but the abundance of NPY-IR nerve fibres was very low. Previously, numerous VIPand NPY-containing nerve fibres were found in the human ASG (Gu et al, 1983;Adrian et al, 1984;Higgins and Gosling, 1989;Lange and Unger, 1990;Chapple et al, 1991;Tainio, 1995;Hedlund et al, 1997;Dixon et al, 2000) and in the ASG of many other animal species (Alm et al, 1977(Alm et al, , 1980Stjernquist et al, 1983;Lamano-Carvalho et al, 1986;Moss et al, 1987;Yuri, 1990;Properzi et al, 1992;Iravani and Zar, 1994;Pinho et al, 1994;Ottesen et al, 1995;Domeneghini, 1997, 1998;Chow et al, 1997;Kaleczyc et al, 1999;Czaja et al, 2000;Majewski et al, 2001;Mirabella et al, 2003). The results of the previously mentioned studies can be summarised as follows: in all species the vast majority of VIP-IR nerve fibres were localised in the mucosal layer of the SV, BU and prostate, whereas only sparse VIP-IR nerve fibres were found within the smooth muscle layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible, that VIP plays a role in the regulation of the secretory function of epithelial cells in this and other AGG. Immunoreactivity to SOM was found in a few nerve fibres supplying the human seminal vesicle and prostate (Gu et al, 1983;Chapple et al, 1991;Crowe et al, 1991;Tainio, 1995). Mirabella et al (2003) revealed SOM-IR nerve fibres innervating the prostate in the water buffalo.…”
Section: Discussionmentioning
confidence: 94%
“…The human prostate receives a dense sympathetic innervation (Chapple et al, 1991) and stimulation of sympathetic nerves (Guh et al, 1995) or the exogenous administration of the sympathetic neurotransmitter noradrenaline causes contraction of human prostatic smooth muscle via al-adrenoceptors (Hieble et al, 1985). It is believed that this stimulation of prostatic al-adrenoceptors gives rise to the 'dynamic' component of bladder outlet obstruction observed in benign prostatic hyperplasia (BPH) and al-adrenoceptor antagonists have proven useful in the symptomatic relief of patients with benign prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 99%